Narrative and design: commemorating the Civil Rights Movement through an inclusive design for Chester I. Lewis Park in Wichita, Kansas - Brown, Skylar (Kansas State University, 2018)
Chester I. Lewis Reflection Square Park is an urban park located on Douglas Avenue within the downtown area of Wichita, Kansas. The Chester I. Lewis Park is a site the city is interested in improving, but no current plans or budget are available. The park has faced issues including a stigma regarding use by the homeless population, vandalism, lack of use by the broader public, and deterioration. Chester I. Lewis was a civil rights lawyer in Wichita, Kansas. One of his cases dealt with the Dockum Drugstore Sit-in, the first successful sit-in of the civil rights movement, which will soon have a new sculpture memorial dedicated a block away from the park. The overall project goal for the downtown park commemorating Lewis’s legacy is to develop a site that will address the current issues with the park and create a connection with the newly developed memorial, all while strengthening the expression of Lewis’s significance as a civil rights leader who championed social integration. The project should develop a sense of place within the community and connect visitors to Wichita’s legacy in the civil rights movement. Methods used by the researcher to build a framework for design consist of archival research into the history of civil rights in Wichita, precedent studies focused on memorials and designing for the homeless, participant observation, a public exhibit with community feedback, and lastly interviews with advocates for the homeless, and living members of the Sit-In. The proposed design for Chester I. Lewis Park demonstrates that it is possible to provide a variety of uses within the park that benefit everyone, including unhoused people who use the park. This site can provide a new outlook for designing inclusively and seeking to remove the stigma that faces the homeless population in Wichita and provide a replicable example of how cities should plan for the homeless in park design.
Keywords: Landscape Architecture; Wichita; Narrative and design; Chester I. Lewis; Homeless; Inclusive